Characterizing defect structures in AM steel using direct electron detection EBSD. (December 2022) - Kacher, Josh; Ruggles, Timothy; Key, Jordan; Nowell, Matthew; Wright, Stuart
Abstract: The mechanical properties of additive and traditionally manufactured alloys are largely dependent on the characteristics and distribution of dislocation cell networks that develop during the fabrication process. This work demonstrates the ability to quantitatively characterize these dislocation structures by high angular resolution electron backscatter diffraction analysis using a direct electron detector. The defect structures are characterized in terms of the geometrically necessary dislocation density and the associated Burgers vector and line direction. The results are discussed in terms of potential defect formation mechanisms. Graphical abstract: Image, graphical abstract